Micromotors Spontaneously Neutralize Gastric Acid for pH‐Responsive Payload Release. (20th January 2017) - Li, Jinxing; Angsantikul, Pavimol; Liu, Wenjuan; Esteban‐Fernández de Ávila, Berta; Thamphiwatana, Soracha; Xu, Mingli; Sandraz, Elodie; Wang, Xiaolei; Delezuk, Jorge; Gao, Weiwei; Zhang, Liangfang; Wang, Joseph
Abstract: The highly acidic gastric environment creates a physiological barrier for using therapeutic drugs in the stomach. While proton pump inhibitors have been widely used for blocking acid‐producing enzymes, this approach can cause various adverse effects. Reported herein is a new microdevice, consisting of magnesium‐based micromotors which can autonomously and temporally neutralize gastric acid through efficient chemical propulsion in the gastric fluid by rapidly depleting the localized protons. Coating these micromotors with a cargo‐containing pH‐responsive polymer layer leads to autonomous release of the encapsulated payload upon gastric‐acid neutralization by the motors. Testing in a mouse model demonstrate that these motors can safely and rapidly neutralize gastric acid and simultaneously release payload without causing noticeable acute toxicity or affecting the stomach function, and the normal stomach pH is restored within 24 h post motor administration.